1974
DOI: 10.1073/pnas.71.8.3221
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Assembly of Aspartate Transcarbamoylase from Catalytic and Regulatory Subunits

Abstract: A scheme for the assembly of aspartate transcarbamoylase (EC 2.1.3.2; carbamoylphosphate:Laspartate carbamoyltransferase) from catalytic and regulatory subunits is presented along with a technique for detecting intermediates and measuring the kinetics of assembly at protein concentrations of about 10 nM. 1251_ labeled subunits (108 cpm/pg) were used, and the reaction was "stopped" at specific times with an appropriate "chase" followed by electrophoretic separation and measurement of the amounts of the various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In earlier studies on the structure and properties of C2R2 we observed that storage of C2R2 for several weeks in 50 mM Tris.HCI containing 2 mM 2-mercaptoethanol at pH 7.5 led to its partial conversion into a mixture of ATCase and free C subunits (23). Moreover, the disproportionation of C2R2 was more rapid in low ionic strength buffers (5 mM Tris.HCI) and was markedly accelerated upon the addition of PALA (24).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In earlier studies on the structure and properties of C2R2 we observed that storage of C2R2 for several weeks in 50 mM Tris.HCI containing 2 mM 2-mercaptoethanol at pH 7.5 led to its partial conversion into a mixture of ATCase and free C subunits (23). Moreover, the disproportionation of C2R2 was more rapid in low ionic strength buffers (5 mM Tris.HCI) and was markedly accelerated upon the addition of PALA (24).…”
mentioning
confidence: 99%
“…Very little exchange of either C or R subunits occurred even in the presence of the bisubstrate analog, N-(phosphonacetyl)-L-aspartate (PALA), which promotes the conformational transition of ATCase to the relaxed state (20,21). Studies were conducted, therefore, on the effect of this active-site ligand on the bonding domains in ATCase-like molecules lacking one R subunit (22)(23)(24)(25). This R-deficient species, designated C2R2, which exhibits both cooperativity and inhibition by CTP (22,23), is an intermediate in both the in vitro assembly of ATCase from subunits and the dissociation of the enzyme (24,26 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations